KLF4 is an epigenetically modulated, context-dependent tumor suppressor - Frazzi, Raffaele (Frontiers in Cell and Developmental Biology, 2024)
The epigenetic layer of regulation has become increasingly relevant in the research focused on tumor suppressors. KLF4 is a well-described zinc-finger transcription factor, mainly known for its role in the acquisition of cell pluripotency. Here we report and describe the most relevant epigenetic regulation mechanisms that affect KLF4 expression in tumors. CpG island methylation emerges as the most common mechanism in several tumors including lung adenocarcinoma, hepatocellular carcinoma, non-Hodgkin lymphomas, among others. Further layers of regulation represented by histone methylation and acetylation and by non-coding RNAs are described. Overall, KLF4 emerges as a crucial target in the fight against cancer.